AB0344 COMPARATIVE ANALYSIS OF SIDE EFFECTS BETWEEN PATIENTS TREATED WITH AND WITHOUT CORTICOSTEROID AT DMARDS-STARTING POINT. SINGLE CENTER RETROSPECTIVE REAL WORLD DATA ANALYSIS. (June 2019) - Ogasawara, Michihiro; Shimada, Yosuke; Abe, Yoshiyuki; Yamaji, Ken; Hori, Satoshi; Tamura, Naoto
Abstract : Background: In the EULAR recommendation on rheumatoid arthritis (RA) treatment, short-term steroid combination should be considered at the start of DMARDs treatment. In this study, we analyzed the present condition of steroid combined use in Japan and the actual situation of side effects in recent years. Objectives: RA patients who started treatment with DMARDs at our hospital during July 2008 to April 2018, Methods: A new incidence of hypertension (HTN), diabetes (DIB), dyslipidemia (HLP), infection (INF) were compared between the two groups of steroid combined use group (D_PSL) and noncombined group (D_nonPSL) and analyzed by Cox regression analysis. The cases had there complications before the start of RA treatment were excluded from the analysis. Results: The number of cases of analysis was 573 (D_PSL = 216, D_nonPSL = 357, average observation period: 5.22±2.70 year), and the new incidence of each complication was INF 50/561 (D_PSL 16.2%vs. D_nonPSL 4.56%[16/351], p=0.000094), HTN 48/527 cases (13.3%[25/188] vs.6.78%[23/339], P = 0.0148), DIB 24/558 (6.16%[13/211] vs. 3.17%[11/347], p = 0.136), HLP 72/542 (15.8%[32/202] vs. 11.8%[40/340], p = 0.198). The incidence of INF was high in D_PSL group in both groups over 65 and under 65 years old (p = 0.00658, p = 0.00267), HTN was high in D_PSL group only in group over 65 years old ( p= 0.0276, p = 0.0554 ). Average starting amount of steroids was 6.07±10.2 mg, cases of non-withdrawal of steroid at 1, 2, 3 years later is 79.7%, 72.2% and 66.3% respectively. Conclusion: Combined use of steroid at the start of DMARDs increased the rate of mortality of infection requiring hospitalization and hypertension. More than half of them were difficult cases of withdrawal of steroids. From the viewpoint of side effect, it is necessary to study the optimization of steroid therapy in the future. Disclosure of Interests: Michihiro Ogasawara: None declared, Yosuke Shimada: None declared, Yoshiyuki Abe: None declared, Ken Yamaji: None declared, Satoshi Hori: None declared, Naoto Tamura Grant/research support from: Astellas Pharma Inc., Asahi Kasei Pharma, AYUMI Pharmaceutical Co., Chugai Pharmaceutical Co. LTD, Eisai Inc., :Takeda Pharmaceutical Company Ltd., Speakers bureau: Janssen Pharmaceutical K.K., Bristol-Myers Squibb K.K., :Mitsubishi Tanabe Pharma Co.